2017
DOI: 10.7717/peerj.3716
|View full text |Cite
|
Sign up to set email alerts
|

Current practice in the management of new-onset atrial fibrillation in critically ill patients: a UK-wide survey

Abstract: BackgroundNew-onset atrial fibrillation (AF) is the most common arrhythmia in critically ill patients. Although evidence base and expert consensus opinion for management have been summarised in several international guidelines, no specific considerations for critically ill patients have been included. We aimed to establish current practice of management of critically ill patients with new-onset AF.MethodsWe designed a short user-friendly online questionnaire. All members of the Intensive Care Society were invi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 36 publications
1
38
0
1
Order By: Relevance
“…Practices also vary according to country: a survey of intensivists in the United Kingdom found that > 80% would choose amiodarone as first-line treatment, whereas 12% chose BBs. 49 Despite being a less commonly used initial treatment, preliminary BB use for AF was associated with a lower risk of in-hospital mortality compared with CCBs, digoxin, or amiodarone in an observational analysis among patients with sepsis. 50 In addition, a study using granular ICU data showed that initial use of metoprolol for AF with RVR was associated with lower need for administration of a second agent compared with amiodarone and better rate control at 4 h compared with diltiazem.…”
Section: Medication Options For Rate and Rhythm Controlmentioning
confidence: 93%
“…Practices also vary according to country: a survey of intensivists in the United Kingdom found that > 80% would choose amiodarone as first-line treatment, whereas 12% chose BBs. 49 Despite being a less commonly used initial treatment, preliminary BB use for AF was associated with a lower risk of in-hospital mortality compared with CCBs, digoxin, or amiodarone in an observational analysis among patients with sepsis. 50 In addition, a study using granular ICU data showed that initial use of metoprolol for AF with RVR was associated with lower need for administration of a second agent compared with amiodarone and better rate control at 4 h compared with diltiazem.…”
Section: Medication Options For Rate and Rhythm Controlmentioning
confidence: 93%
“…Although anticoagulation is a common therapy for AF in the general ward [29], few studies have assessed anticoagulation for treating new-onset AF in the ICU [4,17,19]. ICU physicians may consider anticoagulation for prolonged AF duration based on indirect evidence in the general ward setting [20].…”
Section: Discussionmentioning
confidence: 99%
“…Designing a good clinical trial needs comprehensive information on the clinical course after the identification of a disease. Regarding the clinical course after the identification of new-onset AF in critically ill patients, various strategies for new-onset AF management were reported [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these recommendations, a nationwide survey of intensive care clinicians revealed that 63.8% of clinicians would not routinely anticoagulate critically ill patients with NOAF while 30.8% would consider anticoagulation if NOAF persisted beyond 72 hours rather than the recommended 48 hours by NICE. 13 Furthermore, 98% of critical care clinicians revealed that they would be happy to administer Heparin as anticoagulation but not an oral anticoagulation. 13 The variation in practice likely represents the unique challenges of managing NOAF in critically unwell patients, in which administration of oral anticoagulants may not possible in sedated patients or via nasogastric tube and highlights the need for guidelines specific to critically ill patients.…”
mentioning
confidence: 99%
“…13 Furthermore, 98% of critical care clinicians revealed that they would be happy to administer Heparin as anticoagulation but not an oral anticoagulation. 13 The variation in practice likely represents the unique challenges of managing NOAF in critically unwell patients, in which administration of oral anticoagulants may not possible in sedated patients or via nasogastric tube and highlights the need for guidelines specific to critically ill patients.…”
mentioning
confidence: 99%